FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU SMK KESEHATAN BHAKTI HUSADA BLORA - Sunardi Sunardi (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Sunardi, 2018. “Factors That Affect The Performance Of Teachers SMKBhakti Husada Blora”, Slamet Riyadi University, Surakarta, Thesis,unpublised.The purpose of this research is to know the factors that affect the performanceof teachers SMK Bhakti Husada Blora. In the world of education performanceteacher holds an important role. The success of the renewal of the schoollargely determined by the performance of teachers. The performance is a topachievement of the objectives of the organization which may take the form ofquantitative or qualitative output, creativity, flexibility, dependability, or otherthings that are desired by the organization. This study used a qualitativeapproach. Research conducted at SMK Bhakti Husada Blora. Data analysisusing interactive data analysis i.e. analysis which takes place concurrentlywith the data collection process. The results of this research is the mentalattitude of teachers: teachers work discipline SMK Bhakti Husada Blora ishigh, the motivation of working is quite large and the work ethic is goodenough. Level of education: formal education meets the specified standards,education and training, Bintek and seminars is still lacking. The skills ofteachers that includes the making of a daily work plan (RKH), masterylearning methods, and the grading system is quite good. The supervision ofthe head of school: the school principal has been carrying out theconstruction, supervision and assessment of the teachers at SMK BhaktiHusada Blora. Management leadership: the head of school has been carryingout supervision of learning and performance assessment leadership style on aregular basis, the head of the school is quite good. Health: in general physicalhealth and mental Health of the teachers SMK Bhakti Husada is quite good,but there is no guarantee of good health from health insurance nor the BPJSincurred by the school. Social security: schools have not been able to providesocial security for Health teachers SMK Bhakti Husada Blora. The mastery ofinformation technology: SMK Bhakti Husada Health has not been optimallyutilizing the technology information system to carry out the study as well asservice to the community. The opportunity: an accomplished teachers lesscompeted to improve his work.Key words: teacher, performance, assessment